From Derek Price’s Network of Scientific Papers to Advanced Science Mapping - Moed, Henk F (Applied Evaluative Informetrics, 2017)
This chapter presents two visionary papers published by Derek de Solla Price, the founding father of the science of science. It presents his view on the scientific literature as a network of scientific papers, and introduces important informetric concepts, including ‘research front’ and ‘immediacy effect’. Next, the chapter shows how his pioneering work on modelling the relational structure of subject space evolved into the creation of a series of currently available, advanced science mapping tools.